TEACHING READING USING FIX-UP STRATEGY IN READING COMPREHENSION - Nelvia Ibrahim; Kurnia Budiyanti (Jurnal Cakrawala Ilmiah, 2025)
The purpose of this article is to describe how to teach reading using the fix-up strategy. For a variety of reading objectives, teachers have used a wide range of instructional tactics. In the meanwhile, it aids readers in fulfilling their reading goals. The fix-up strategy was suitable for solving the issue pertaining to the metacognitive process through readers' comprehension. During text processing, these strategies help readers recognize comprehension challenges and apply focused understanding.